Quality of Life among Caregivers of Lower-Income Cancer Patients: A Single-Institutional Experience in India and Comprehensive Literature Review - Vishal Vashistha; Rosemary Poulose; Chandrashekhar Choudhari; Sukhdeep Kaur; Anant Mohan (Asian Pacific Journal of Cancer Care, 2019)
Objectives: Quality of life (QOL) among caregivers of cancer patients is often diminished. For lower-income caregivers, the deterioration in QOL may be of greater impact. We aimed to evaluate QOL among lower-income cancer caregivers in Delhi, India and to comprehensively review similar investigations conducted internationally. Methods: A Hindi-version of the Caregiver Quality of Life Cancer (CQOLC) index was administered to 89 caregivers of lung cancer patients. Bivariate analyses were employed to evaluate associations between baseline demographics and CQOLC index scores. A systematic review of PubMed, EMBASE, and PsychInfo was undertaken. Results: Reduced QOL was observed for caregivers residing in homes earning less than our center’s median annual income per capita (p < 0.01) and for caregivers providing aid for 4 months or longer (p < 0.01). The burden of caregiving contributed most to summative index scores (p < 0.01). Eleven studies were selected by systematic review. Lower-income caregivers in Asia and the Middle East experience reduced QOL and increased burden. Available evidence does not suggest that lower-income caregivers in Europe and North America share worse QOL. Conclusion: Lower-income caregivers suffer loss in QOL, particularly in the developing world. Resourceful interventions are warranted to mitigate burden for this underappreciated population.